“Basic Science” in Upper Secondary School Education in Japan. II. The Structure of “Basic Science” and Examples of a Teaching Program. - Ito, Nobutaka; Nakayama, Hisako; Shibanuma, Susijmu; Shirai, Minoru; Oki, Michinori (Science Education)
The article discusses the structure of "Basic Science" and examples of a teaching program in upper secondary school education in Japan. Some teaching topics in "Basic Science" are "light and substances" and "the earth and living things," which are closely related to topics taught in lower secondary school science education. These teaching topics are divided into eight major items such as light, energy, structure of matter, chemical reactions, universal gravitation and the solar system, structure of the earth, life and substances, and evolution. The eight major items are numbered from one to eight, as stated in points for consideration in handling and teaching the content, this order does not restrict the sequence of instruction or the manner of grouping topics.